CHARACTER EDUCATION MODEL FOR EARLY CHILHOOD BASED ON E-LEARNING AND CULTURE OF JAVA - Kusumandari, Rafika Bayu (Indonesian Journal of Early Childhood Education Studies, 2013)
Character education will be more meaningful if carried out since early childhood. This is because early childhood education is the foundation of the character formation of children. In the implementation of early childhood character education tailored to the characteristics of each school and the emphasis of each agency arrangements for early childhood education, culture-based Java. Javanese culture needs to be introduced early on to avoid losing out to erode the culture that goes along with globalization. In addition, Java is promoting cultural etiquette and manners are very suitable for the character formation of childrens early childhood.